Catalysis via Induced Intramolecularity: Carbonyl-catalyzed Hydration of α-Amino Nitriles - Hussain, Bashir (Université d'Ottawa / University of Ottawa, 2014)
In the last decade, there has been a surge of interest from the chemistry community in developing synthetic catalysts that emulate the remarkable rate accelerations observed for enzymatic reactions. One approach utilized by enzymes involves preorganization of substrate(s) using a favourable binding event to orient the substrate(s) in a reactive arrangement. Although the “induced intramolecularity” is entropically unfavourable, it is facilitated by the enzymes and utilized to accelerate the subsequent chemical transformation. Chemists have often used a conceptually related stepwise approach in which temporary tethers are assembled to induce a temporary intramolecularity. This preorganization often enables difficult intermolecular reactions, and typically leads to increased regio-, chemo-, and stereoselectivity in chemical reactions. Seeking to develop a catalytic approach, we focused our efforts in developing a mild, carbonyl-catalyzed hydration protocol for - and -amino nitriles to give the corresponding - and -amino amide and acid. This work highlights the value of employing induced intramolecularity in accessing structurally important chemical motifs that otherwise require harsh reaction conditions. Additionally, this thesis presents the background material, design process, optimization and scope of this reactivity.
Keywords: enzyme; preorganization; preassociation; nitrile; amide; intramolecular; tether; catalysis